Nanoparticles-mediated ion channels manipulation: from their membrane interactions to bioapplications - Huang, Qiwen (2023)
Ion channels are transmembrane proteins ubiquitously expressed in all cells that control various ions (e.g. Na+, K+, Ca2+ and Cl- etc) crossing cellular plasma membrane, which play critical roles in physiological processes including regulating signal transduction, cell proliferation as well as excitatory cell excitation and conduction. Abnormal ion channel function is usually associated with dysfunctions and many diseases, such as neurodegenerative disorders, ophthalmic diseases, pulmonary diseases and even cancers. The precise regulation of ion channels not only helps to decipher physiological and pathological processes, but also is expected to become cutting-edge means for disease treatment. Recently, nanoparticles-mediated ion channel manipulation emerges as a highly promising way to meet the increasing requirements with respect to their simple, efficient, precise, spatiotemporally controllable and non-invasive regulation in biomedicine and other research frontiers. Thanks the advantages of their unique properties, nanoparticles can not only directly block the pore sites or kinetics of ion channels through their tiny size effect, and perturb active voltage-gated ion channel by their charged surface, but they can also act as antennas to conduct or enhance external physical stimuli to achieve spatiotemporal, precise and efficient regulation of various ion channel activities (e.g. light-, mechanical-, and temperature-gated ion channels etc). So far, nanoparticles-mediated ion channel regulation has shown potential prospects in many biomedical fields at the interfaces of neuro- and cardiovascular modulation, physiological function regeneration and tumor therapy et al. Towards such important fields, in this typical review, we specifically outline the latest studies of different types of ion channels and their activities relevant to the diseases. In addition, the different types of stimulation responsive nanoparticles, their interaction modes and targeting strategies towards the plasma membrane ion channels will be systematically summarized. More importantly, the ion channel regulatory methods mediated by functional nanoparticles and their bioapplications associated with physiological modulation and therapeutic development will be discussed. Last but not least, current challenges and future perspectives in this field will be covered as well.